Pentingnya Manajemen Humas dalam Mendorong Budaya Baca yang Berkelanjutan untuk Peningkatan Budaya Mutu di Lembaga Pendidikan Islam - Ayu Puspitasari; Dwi Utari; Muchammad Eka Mahmud; Akhmad Muadin (Journal on Education, 2023)
Public Relation management plays an important role in building a sustainable reading culture in Islamic educational institutions. A strong reading culture is essential to improving the quality of education as it helps learners develop deep understanding, improve critical thinking skills and broaden their horizons. But in the digital era, many learners tend to be more interested in social media and digital entertainment than reading books or printed sources. The research method used is a qualitative method with a descriptive approach. The purpose of this research is to find out the role of effective public relations management that can help campaign for the importance of reading culture to all stakeholders. The Qur'an and Sunnah provide the foundation and guidelines in seeking knowledge and deep understanding. The results showed that PR management can design effective communication campaigns to motivate school members to be actively involved in reading activities. Public relations management plays an important role in fostering a sustainable reading culture and improving the quality of education in Islamic educational institutions. To achieve this, schools must collaborate with stakeholders. A strong reading culture will influence learners' perceptions of learning, improve their critical thinking skills, and stimulate their interest in seeking knowledge. Thus, reading culture is one of the key elements in developing the quality of Islamic educational institutions